Os elementos determinantes da orientação empreendedora nas universidades públicas federais da região Nordeste do Brasil - Lima, Simone Freitas Araújo (2017)
The transformations evidenced in the public sector over the years demonstrate the increase in the expectations of modernization and this process has been related to the behavioral and managerial notions, imbued with concepts and practices that were own and, until then, restricted to business organizations sphere. One of the perspectives to reach the entrepreneurial behavior is the entrepreneurial orientation (OE), which allows analyze this element relating it to the environment. It is a particular behavior pattern that permeates all organization levels reflecting a strategic philosophy of action. It emerges as an important construct in entrepreneurship scope, because it enables through processes, practices and activities the organizational development based on the strategic decision making, the implantation of entrepreneurial behavior in the corporate environment and, consequently, in the promotion of culture oriented to entrepreneurship. However, it is necessary to consider the peculiarities inherent to public organizations such as universities, which are challenged to remodel the role of knowledge producers, making it a means for their economic growth. This study aimed to analyze the determinants of entrepreneurial orientation in public universities in the Northeast Region of Brazil through the use of an innovative scale developed by Todorovic, McNaughton and Guild (2011) known as ENTRE-U. The target population comprises the faculty members of graduate programs / programs in engineering and computer science. Specifically, it was verified the representativeness of research mobilization, nonconventionality, collaboration with productive sector and university policy dimensions of OE's in these universities; showed the OE practices according to these dimensions and indicated the influence level between these dimensions in federal public universities in that region. It were used quantitative methodology and survey research method. The data were analyzed using exploratory factorial analysis and confirmatory factorial analysis, using the modeling technique or analysis of structural equations to confirm the theoretical model and compare it with the one identified in this study. Among the main results obtained, it was observed the dimension that best represented the OE was the research mobilization and the practices evidenced by this dimension have as main focus the student's involvement for the participation in applied research. The dimensions, in spite of their individual characteristics, influence each other and positively the OE, so due attention must be paid to management practices of each of them when one has in mind the overall result. The model proposed by this research presents good results when compared to the theoretical model studied, although it did not reach the ideal level of adjustment. The factorial analyzes show similar results among themselves, and these results are also similar to those shown by the creators of the scale, being able to evidence the scale as a valid instrument of OE research in public universities.